A noção platônica de imagem (Argos, 2025)
How the notion of image is described in Plato's Dialogues and which relationship it has with the knowledge, the truth and the being? By reading how the images of the sun, the line and the cave are constructed in books VI-VII of The Republic, we can find out the answers to questions about the intriguing and disconcerting platonic notion of image.
Keywords: Plato; The Republic; image; the sun, the line and the cave